Clicking molecular hooks on silica nanoparticles to immobilize catalytically important metal complexes: the case of gold catalyst immobilization - Ganai, Anal Kumar; Bhardwaj, Rima; Hotha, Srinivas; Sen Gupta, Sayam; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
Gold mediated reactions have emerged as one of the best choices for affecting a variety of chemical transformations with a wide range of functional group tolerance. Application of such transformations to industrial processes necessitates immobilization of the Au ions into a matrix for easy separation of the catalyst after reaction. We report the synthesis and characterization of silica nanoparticles in which Au(III) has been immobilized through a 1,2,3-triazole linkage using an alkynalated picolinic acid exploiting ``click chemistry''. The Au( III) immobilized silica nanoparticle has been thoroughly characterized using FT-IR, C-13 CP MAS NMR and XPS. The utility of these particles as an easily separable catalyst for the Hashmi phenol synthesis is also reported.